Digital literacies in in-service and pre-service teacher education: some considerations on the learning provided by such process - Nascimento, Ana Karina de Oliveira (Revista Leitura, 2019)
This paper aims at discussing continuing and pre-service teacher education, when it comes to teachers’ everyday practices that involve digital literacies, as defined by Lankshear and Knobel (2008). It is a qualitative-interpretative analysis, a result of data collected through questionnaires, interviews and class recordings during an inservice teacher education project but which focuses on the questionnaires answered by undergraduate English students from a federal university in Brazil working on the same group. The results point to the fact that it is beneficial providing pre-service education connected to in-service experiences, when the focus is on digital literacies. DOI: 10.28998/2317-9945.2014v1n53p19-38